“SO FAR AWAY” * How Doctors Can Contribute to Making Endometriosis Hell on Earth. A Call for Humanistic Medicine and Empathetic Practice for Genuine Person-Centered Care. A Narrative Review - Cetera GE; Facchin F; Viganò P; Merli CEM; Frassineti A; Fiorini J; Somigliana E; Vercellini P (Dove Medical Press, 2024)
Giulia Emily Cetera,1,2 Federica Facchin,3 Paola Viganò,2,4 Camilla Erminia Maria Merli,1 Annalisa Frassineti,5 Jessica Fiorini,5 Edgardo Somigliana,2,4 Paolo Vercellini1,2 1Gynecology Unit, Fondazione IRCCS Ca’ Granda Ospedale Maggiore Policlinico, Milan, Italy; 2Academic Center for Research on Adenomyosis and Endometriosis, Department of Clinical Sciences and Community Health, Università degli Studi di Milano, Milan, Italy; 3Department of Psychology, Catholic University of the Sacred Heart, Milan, Italy; 4Infertility Center, Fondazione IRCCS Ca’ Granda Ospedale Maggiore Policlinico, Milan, Italy; 5Associazione Progetto Endometriosi Organizzazione di Volontariato, Reggio Emilia, ItalyCorrespondence: Giulia Emily Cetera, Gynecology Unit, Fondazione IRCCS Ca’ Granda, Ospedale Maggiore Policlinico, via della Commenda 12, Milano, 20122, Italia, Tel +392550352318, Email giuliaemily.cetera@gmail.comAbstract: The distance physicians may create within the relationship with their patients by not having a humanistic approach to their practice may strongly influence clinical outcomes. The purpose of this paper is to convey the well-known narrative of patient dissatisfaction into pro-action by discussing the aspects of dehumanization, which may occur in the relationship between physicians and women with endometriosis. Eight dimensions of dehumanization are examined and related to everyday scenarios occurring in endometriosis care settings and the possible downstream consequences on patients’ clinical outcomes are described. Objectification, which may come across as minimization of pain, may not only increase patients’ perception of pain but also lead to undertreatment of unrecognized forms of endometriosis, especially among adolescents. Passivity, that is not favoring shared decision-making nor self-management, may compromise adherence to treatment, reducing patients’ trust in physicians and quality of life. The same consequences may result from homogenization, that is giving for granted that all patients have the same access to care. Both isolation, ie not practicing therapeutic empathy, and loss of meaning, ie not supporting patients in the re-definition of their life plans, may affect women’s psychological wellbeing and further increase pain perception. Ignoring women’s personal journey by not providing clear information on the consequences endometriosis may have on their lives may favor women’s self-silencing. Not promoting an un-biased communication and not setting aside scientific polarization are the main features of dislocation, which may jeopardize patient empowerment. Lastly, having a reductionist approach to the body may contribute to chronicization of pain, thus compromising quality of life. This considered, taking time to listen to women with endometriosis and tailoring decisions on the basis of their individual needs should be fostered as a moral duty. Physicians should always keep in mind that they are not only deliverers of treatment; they are a form of treatment themselves.Keywords: endometriosis, dehumanization, patient-centered care, treatment, phsycians’ role